2018
DOI: 10.3390/su10030766
|View full text |Cite
|
Sign up to set email alerts
|

Energy Use and Perceived Indoor Environment in a Swedish Multifamily Building before and after Major Renovation

Abstract: Improved energy efficiency in the building sector is a central goal in the European Union and renovation of buildings can significantly improve both energy efficiency and indoor environment. This paper studies the perception of indoor environment, modelled indoor climate and heat demand in a building before and after major renovation. The building was constructed in 1961 and renovated in 2014. Insulation of the façade and attic and new windows reduced average U-value from 0.54 to 0.29 W/m2·K. A supply and exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The high humidity in building materials (which causes condensation on surfaces) must be differentiated from the humidity in the air in the living spaces. Several studies have associated slightly increased air humidity in houses or offices with beneficial effects on health and work capacity [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The high humidity in building materials (which causes condensation on surfaces) must be differentiated from the humidity in the air in the living spaces. Several studies have associated slightly increased air humidity in houses or offices with beneficial effects on health and work capacity [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive renovation with additional ventilation measures comprises scenario 2. The renovation package of scenario 2 also includes the measures carried out in 2014, and previously studied by La Fleur et al [71,79]. Furthermore, scenario 3 consists of a substitution from DH to GSHP, scenario 4 adds measures on the envelope and, lastly, added ventilation measures make up scenario 5.…”
Section: The Reference Building and Renovation Scenariosmentioning
confidence: 99%
“…The analysis is based on the geometry of an existing 1960s building located in central Linköping, Sweden. The building underwent renovation in 2014, and the effects on the building from the renovation have been previously been studied with regard to energy demand and indoor environment, using an empirically validated whole building energy simulation model [16,50]. To address the choice between energy renovation and the demolition and construction of a new building with regard to the differences in thermal performance, three additional construction types have been included in the analysis.…”
Section: Case Descriptionmentioning
confidence: 99%
“…The potential for a reduction in energy 2 of 27 use from insulation is revealed to be enormous. A significant reduction in heat demand has also been achieved by installing a balanced mechanical ventilation system with heat recovery as part of buildings renovation [12,13,16]. Several studies have shown that the implementation of EEMs in energy renovation of buildings have the potential to reduce the energy demand to a low energy building, passive house, or nearly-zero energy building standard [6,9,17,18].…”
Section: Introductionmentioning
confidence: 99%